2012
DOI: 10.1519/jsc.0b013e318241382a
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Differences in Strength and Power Between Different Levels of Competition in Rugby Union Athletes

Abstract: Levels of strength and power have been used to effectively discriminate between different levels of competition; however there is limited literature in rugby union athletes.To assess the difference in strength and power between levels of competition, 112 rugby union players including 43 professionals, 19 semi-professionals, 32 academy level, and 18 high school level athletes, were assessed for bench press and box squat strength, and bench throw and jump squat power. High school athletes were not assessed for j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
101
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(114 citation statements)
references
References 30 publications
9
101
0
4
Order By: Relevance
“…Whilst the latter mentioned studies used field-based methods, the current study provides comparative data derived from laboratory based measures, including an accurate assessment of peak power and is the first to report these measures in rugby union academy players. The changes in jump height and peak power can be explained due to the adaptation of growth and maturation processes, and the stimulus provided by strength and power training programs which have reported increased power output with increased levels of maximal strength (2,4,6). Such types of programmes are commonplace in regional rugby union academies, with the relationship between maximal strength and jump height well reported (30, 37).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whilst the latter mentioned studies used field-based methods, the current study provides comparative data derived from laboratory based measures, including an accurate assessment of peak power and is the first to report these measures in rugby union academy players. The changes in jump height and peak power can be explained due to the adaptation of growth and maturation processes, and the stimulus provided by strength and power training programs which have reported increased power output with increased levels of maximal strength (2,4,6). Such types of programmes are commonplace in regional rugby union academies, with the relationship between maximal strength and jump height well reported (30, 37).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some studies only use gym-based strength assessments (4)(5)(6); whereas tests such as the isometric mid-thigh pull (IMTP) using a portable force plate allows measures of maximal strength (peak force). Peak force measures, derived from the IMTP may further develop the understanding of the physical profiles of rugby union players by age category, as maximal strength has been demonstrated as a discriminating factor between playing levels (2,4,6) and between age categories (40, 41). Further, the IMTP has found significant correlations with dynamic performance in a number of sports, including Olympic weightlifting (27), sprint cycling (38) and more recently in rugby league players (44), with the latter suggesting that it may be a useful monitoring tool for both strength and power.…”
Section: Introductionmentioning
confidence: 99%
“…Baker and Newton [56] found correlations between changes in the deep squat 1 RM and changes in the power output in jump squats (40-100 kg) of r = 0.83-0.96 over a 4-year period. Given that the highest power values are found in athletes with a high maximal strength level, it is obvious that the development of maximal strength must be considered a decisive factor in the long-term training process [28,50,55,56,73,74,77,79,80,82,87,101,[117][118][119].…”
Section: Effects Of Different Periodization Models On Strength and Spmentioning
confidence: 99%
“…The higher the strength level of an athlete is, the less a further increase in the maximal strength will contribute to Short-term Periodization for Speed-strength Events an improvement in power output and speed-strength performances [55,57,74,94,101,109,[120][121][122][123]. The intervention periods that are cited in Sects.…”
Section: Effects Of Different Periodization Models On Strength and Spmentioning
confidence: 99%
“…3 Given the importance of physical qualities for match performance 1,2 , limited studies exist that consider the height, body mass, and physical characteristics of netball players. The results of several studies have demonstrated that differences in performance characteristics exist between playing levels within rugby league 4,5 , rugby union 6,7 , and lacrosse 8 . Surprisingly, no study has examined the height, body mass, and physical characteristics of academy netball players.…”
Section: Introductionmentioning
confidence: 99%